1987
DOI: 10.1002/j.1556-6676.1987.tb01291.x
|View full text |Cite
|
Sign up to set email alerts
|

Career Indecision: A Family Systems Perspective

Abstract: In existing theories of vocational development career indecision is generally attributed to character deficits in the young adult. The authors present an alternative, family systems perspective on career indecision. Also, they speculate on the family patterns that contribute to career indecisiveness and on the functions that this problem may serve within the larger family network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

15
99
4
8

Year Published

1990
1990
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(128 citation statements)
references
References 30 publications
15
99
4
8
Order By: Relevance
“…In a similar way, Zingaro (1983) pointed out that subjects who presented pronounced difficulties in the career-choice process seem to evidence an undifferentiated self and a high degree of intergenerational fusion between parents and children (Bowen, 1978). Also using a systemic framework, Lopez and Andrews (1987) considered that career development and choice in adolescence cannot be separated from two important developmental tasks of this period: the construction of identity and psychological separation from the family. They emphasize how problems in the differentiation of the adolescent's self from the family system can be manifest as career indecision.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…In a similar way, Zingaro (1983) pointed out that subjects who presented pronounced difficulties in the career-choice process seem to evidence an undifferentiated self and a high degree of intergenerational fusion between parents and children (Bowen, 1978). Also using a systemic framework, Lopez and Andrews (1987) considered that career development and choice in adolescence cannot be separated from two important developmental tasks of this period: the construction of identity and psychological separation from the family. They emphasize how problems in the differentiation of the adolescent's self from the family system can be manifest as career indecision.…”
mentioning
confidence: 98%
“…
Lopez and Andrews (1987) interpreted career indecision as an indicator of the inadequate psychological separation of adolescents from their parents. However, various empirical studies have not managed to clearly demonstrated evidence of a relationship between systemic family variables and career indecision.
…”
mentioning
confidence: 99%
See 3 more Smart Citations